2022
DOI: 10.1055/s-0041-1741376
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Different Occlusal Loading on Six Restorative Materials for Restoration of Abfraction Lesions—Finite Element Analysis

Abstract: Objectives The aim of the study was to analyze the occurrence of stress on teeth with abfraction lesions restored with six different restorative materials, and by introducing the tensile strength parameters to calculate the safety factor of the material under the load (ratio between the strength of the material and the maximum stress). Materials and Methods Three-dimensional models of the mandibular premolar are created from a microcomputed tomography images. An abfraction lesion is modeled on the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Many authors consider that, although time-consuming, FEA analysis helps us to explain the occurrence of a series of unwanted phenomena at the level of some teeth, implants, direct or indirect restorations, and the dental materials used, and can indicate the vulnerable areas where maximum stresses and deformations are developed [57][58][59][60][61][62]. Jakupović A. et al [63] found that the type of tooth loading has the greatest influence on the intensity of stress. The values of the obtained stresses in the restorative material and dental tissues differ due to the different mechanical properties of the materials.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors consider that, although time-consuming, FEA analysis helps us to explain the occurrence of a series of unwanted phenomena at the level of some teeth, implants, direct or indirect restorations, and the dental materials used, and can indicate the vulnerable areas where maximum stresses and deformations are developed [57][58][59][60][61][62]. Jakupović A. et al [63] found that the type of tooth loading has the greatest influence on the intensity of stress. The values of the obtained stresses in the restorative material and dental tissues differ due to the different mechanical properties of the materials.…”
Section: Discussionmentioning
confidence: 99%
“…Since the intensity of occlusal force and teeth contact surface is extremely variable, two occlusal contact types were chosen. The stress of the simulated axial and oblique load was 200 N [32][33][34][35] (►Fig. 2A and B).…”
Section: Methodsmentioning
confidence: 99%
“…They unanimously established that the term “abfraction” should not be used anymore because there is not enough information to demonstrate that this form of dental wear is determined by a single process [ 8 ]. Despite their recommendation, the term is still used, suggesting the role of occlusal stress in the etiology of these lesions [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%